Process design and economics for the conversion of lignocellulosic biomass into jet fuel range cycloalkanes. (1st July 2018) - Yang, Zixu; Qian, Kezhen; Zhang, Xuesong; Lei, Hanwu; Xin, Chunhua; Zhang, Yayun; Qian, Moriko; Villota, Elmar
Abstract: The economic feasibility of a facility producing jet fuel range cycloalkanes, hydrogen and biochar via microwave-assisted catalytic pyrolysis integrated with mild hydrogenation was evaluated by modeling a 1000 metric dry tonne feedstock/day using ASPEN PLUS®. The effects of hydrogenation solvent, heat integration, and coproducing H2 or syngas were investigated in different analysis scenarios. The results indicated that the production of jet fuel could reach 47882.74 Gallon/day, with 9.58 Metric tonne/day biochar and 28200 kg/day H2 as coproducts. The lowest minimum selling price of 3.78 $/Gallon was obtained when using n -hexane as the hydrogenation solvent and coproducing H2 with heat integration. The sale of H2 offset the high production cost, resulting in a significant decrease in the minimum selling price. Sensitivity analysis indicated that the production process was greatly sensitive to total capital investment, internal rate of return, market prices of feedstock and H2 . Highlights: TEA of the jet fuel production from microwave catalytic pyrolysis of biomass. High capital investment can be offset by coproduct credits. TCI, IRR and prices of feedstock and H2 strongly affect the production cost. The process can compete with other bio jet fuel production processes.